ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PESERTA BPJS DI PUSKESMAS PANDIAN KABUPATEN SUMENEP - Rindi Antina, Rila (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Patient satisfaction as users of services is one indicator in assessing the quality of services at the health center. High satisfaction will show the success of the health center in providing quality health services. After a preliminary study showed that there are patients who are not satisfied with the services provided. The purpose of this study was to analyze the influence of service quality on patient satisfaction BPJS participants in Puskesmas Pandian Sumenep.Type of quantitative research. The study population was a participant at the health center BPJS Pandian Sumenep much as 225 respondents and a sample of 144 respondents. Data collection techniques using variable measurement based questionnaire with Likert scale. Analysis of data using statistical Spearment Rank test.Hypothesis test results Ï value: 0.00 and 0.05 Î± so that it can be concluded that the Ï value <Î± and can be described that the value of H0 that there is a relationship between service quality and patient satisfaction.The results of this study indicate that service quality has a significant influence on patient satisfaction, hence providing health care should pay attention to the quality of services provided. Keywords: Quality of Care, Patient Satisfaction